Adaptation Insights Inception Workshop Report - Njuguna, Lucy; Rosenstock, Todd; Nowak, Andreea C. (2024)
The Adaptation Insights Project, launched at the ILRI Campus in Nairobi on 16 October 2024, aims to close critical gaps in understanding the effectiveness of adaptation in Africa. This report captures dialogue with stakeholders at the inception workshop, outlining demand, ongoing efforts and strategic areas for engagement.